TANGGUNGJAWAB NOTARIS DALAM PENDAFTARAN JAMINAN FIDUSIA SECARA ELEKTRONIK (ONLINE) MENURUT PERATURAN MENTERI HUKUM DAN HAK ASASI MANUSIA DI KANTOR NOTARIS MHD. AFANDI MUARO BUNGO - Dwikornida dan Ihda Fitria (Normative Jurnal Ilmiah Hukum, 2020)
One of the roles of the notary is to serve the interests of the parties, for example, in helping to make a loan agreement. If a debt agreement is burdened with collateral that is only for movable objects, a fiduciary agreement arises as an accecoir agreement whose existence always follows the principal agreement. The responsibility of a notary public in registering fiduciary guarantees electronically (online) is to make a fiduciary guarantee deed, and register a fiduciary guarantee deed until the issuance of a fiduciary guarantee certificate by the fiduciary guarantee registration office. Since March 2013, in line with the enactment of ministerial regulation No. 9 of 2013 concerning the enactment of electronic fiduciary guarantee registration, fiduciary guarantee registration is no longer done manually but by online through the websie director general for registration of fiduciary guarantees.